The United States and China financial communication and the notion of risk - Changjun Zheng; Konan Richard Kouadio; Bienmali Kombate (Journal of Risk and Financial Management, 2021)
The close relationship between governments and their central banks generates risks for both partners. This paper presents an original qualitative empirical approach based on textual analysis of the United States of America, China, and their Central Banks' respective communications. These financial communications are the subject of comparison through a textual analysis to determine these actors' positions in the 'cultural theory' and, more widely, the sociology of risk. The risk profiles identified of the United States of America Federal government and the People's Bank of China do not necessarily correspond to their legal status and economic role. These results also shed light on the fact that the cultural background cannot be separated from the risk perception in these countries. However, an eye needs to be kept on the geopolitics and securities risk factors that can influence the global economy's evolution.
Keywords: 330; central bank; cultural theory; government; risk; textual analysis